Does borderline kidney allograft rejection always require treatment? - Németh, Dorottya; Ovens, Jörg; Opelz, Gerhard; Sommerer, Claudia; Döhler, Bernd; Becker, Luis Eduardo; Groß-Weissmann, Marie-Luise; Waldherr, Rüdiger; Mieth, Markus; Sadeghi, Mahmoud; Schmidt, Jan; Langer, Robert M.; et al. (Transplantation, 2010)
Background. - Borderline rejection (Bord-R) is a frequent diagnosis in renal transplantation, and there is increasing evidence that regulatory T lymphocytes are involved in its pathogenesis. Current histopathologic practice does not differentiate between graft-protecting and -damaging T lymphocytes, and patients with Bord-R routinely receive rejection treatment. We analyzed Treg-associated forkhead box P3 (Foxp3) gene expression in Bord-R and more severe forms of acute rejection episodes (ARE). - Methods. - Foxp3 transcripts were measured in 520 serial peripheral blood samples from 177 kidney graft recipients obtained during the first 20 days posttransplantation. - Results. - The highest Foxp3 transcripts were observed in patients with Bord-R or without rejection and the lowest in patients with ARE. Patients with Bord-R on posttransplant days 5 to 7 showed an increased Foxp3 transcript level of 156%, which increased to 302% by posttransplant days 14 to 16. In contrast, patients with ARE demonstrated significantly lower Foxp3 gene expression than that observed in Bord-R, nonrejectors, or acute tubular necrosis patients (P=0.001, P<0.001, and P=0.005, respectively, on days 11-13). Acute tubular necrosis patients demonstrated intermediately high Foxp3 gene expression. - Conclusions. - Our data indicate that increased Treg activity in peripheral blood is a frequent feature of Bord-R. This finding questions the appropriateness of rejection treatment in all patients with the histopathologic diagnosis “Bord-R”.